Rectal band ligation as a treatment for chronic radiation proctitis: a feasibility study - Lamonaca, Laura; Auriemma, Francesco; Paduano, Danilo; Bianchetti, Mario; Spatola, Federica; Galtieri, Piera; Maselli, Roberta; Repici, Alessandro; Mangiavillano, Benedetto (Endoscopy International Open, 2022)
Background and study aims Chronic radiation proctitis (CRP) occurs in 5 % to 20 % of patients undergoing pelvic radiation therapy and frequently manifests with rectal bleeding. Endoscopic management of more severe and refractory cases can be challenging. Rectal band ligation (RBL) has been shown to be a feasible alternative to current available techniques, especially in extensive CRP. Our aim is to evaluate clinical and technical success of RBL.Patients and methods We enrolled all consecutive patients treated with RBL for severe or recurrent hemorrhagic CRP. Success was defined as endoscopic evidence of complete rectal healing and/or cessation of bleeding not requiring further treatment or blood transfusion.Results We enrolled 10 patients (7 males, mean age 75.6 years). Median length of the CRP from the anal verge was 4.5 cm and mean surface area involved was 89 %. Eight patients (80 %) were naïve to endoscopic treatment, while two had undergone argon plasma coagulation (APC). Median follow-up was 136.5 days. Success was achieved in 100 % of patients after a mean number of 1.8 RBL sessions. A mean number of 4.7 bands were released in the first session while a mean of 3.1 and 2 bands were placed in the second and third sessions, respectively. As for adverse events, only one patient reported mild tenesmus and pelvic pain after the procedure.Conclusions RBL is a safe and effective therapeutic modality for the treatment of hemorrhagic CRP. It could be considered a valid first-line option in case of extensive rectal involvement as well as a viable rescue treatment after failed APC.